COMPARATIVE HEMOGLOBIN AND HEMATOCRIT BEFORE AND AFTER DONATION TO BLOOD DONATE IN UNIT TRANSFUSION YOGYAKARTA CITY - Yuli Astuti; Dyah Artini (Jurnal Riset Kesehatan, 2019)
Blood is one of the main components in the human body. The people's need for blood is high, therefore the blood service in Indonesia should have good quality and total services. Unit Transfusion Yogyakarta City is one of the good services in the blood donation. In the blood donation, examination hemoglobin and hematocrit are important to selection for donors. The aim of this study is to determine comparative in hemoglobin and hematocrit levels before and after donors in UTD PMI Yogyakarta City. The type of research used was experimental with cross sectional research design. The sampling technique used was accidental sampling with a total sample of 67 donors. Based on the results of statistical tests on the data obtained, the results obtained with p value less than 0,05 which is significantly different between the hemoglobin level before and after the donor. Based on these result there were differences in hemoglobin and hematocrit levels before and after of blood donation in Unit Transfusion PMI Yogyakarta City.